The good karma of Daily Secret - Foutakoglou, Evangelos, (SAGE Knowledge. Cases., 2013)
This case focuses on the attempt of Daily Secret's founders to keep control of their initial good-karma vision while seeking external funding to accelerate business expansion. The case addresses factors that are typically important for the growth of today's born globals, including trust among employees, the use of the internet, and network and relationship building. It also looks closely at how economic circumstances and culture influence the birth and operations of an entrepreneurial organization. The case concentrates on Daily Secret's two founders, Nikos Kakavoulis and Phaedra Chrousos, and the two strategic options they faced - going back home to resume slow and steady growth without any external investments, maintaining full ownership but with great uncertainty over business sustainability, or accepting the financially attractive offer made by the VC, ensuring sufficient funds to grow at a faster pace but losing the good karma vision that underpinned everything they had built with Daily Secret.